Learning Style Analysis for Differentiated New Paradigm Learning in Public Senior High School 1 Semendawai Suku III East Oku - Nuriz Dariyani; Leni Marlina*; Ida Sriyanti; Sudirman Sudirman; Meilinda Meilinda (Universitas Syiah Kuala, 2022)
Learning with a new paradigm is designed based on the principle of differentiated learning so that each student learns according to their needs and stage of development. This study aims to obtain an overview of the trends in the learning styles of students at public senior high school 1 Semendawai Suku III East Oku. These results are intended for initial assessment in preparing differentiated teaching modules that will be used in differentiated learning. This research is a qualitative descriptive study. The method used is a survey using a learning style questionnaire developed by chislett and chapman. The survey results were then analyzed and grouped by researchers according to the characteristics of students' learning styles, namely visual, auditory, and kinesthetic learning styles. The sample used is class x as much as one class, this class is a model to find out how learning styles can be found in other classes. Based on the results of the study, it was found that every student has a tendency to learn styles, be it visual, audio, or kinesthetic. From the analysis of the learning styles of students at public senior high school 1 semendawai Suku, east oku, the results showed that the tendency of students' learning styles was audio by 46%, visual learning styles by 39%, and kinesthetic learning styles by 15%. These results indicate that in one class the tendency of students' learning styles varies. Differentiated learning needs to be developed by educators in order to facilitate the needs of students' diverse learning styles. These results indicate that in one class the tendency of students' learning styles varies. Differentiated learning needs to be developed by educators in order to facilitate the needs of students' diverse learning styles